ANALISIS PROGRAM SAṀSKṚTA BĀLAKENDRAM SEBAGAI MODEL PENDIDIKAN UNGGUL, RAMAH, DAN TERINTEGRASI PADA PASRAMAN NONFORMAL - Suparta, Ida Kade; Kusumasanthi, Dewi; Pramana, Ida Bagus Kade Yoga (Fakultas Dharma Acarya IAHN-TP Palangka Raya, 2026)
Saṁskṛta Bālakendram has the potential to serve as an excellent, child-friendly, and integrated educational model within non-formal pasraman education in Lombok. However, its sustainability has faced various challenges, eventually leading to the gradual discontinuation of its implementation. This study aims to analyze the program in realizing an excellent, child-friendly, and integrated educational model. A qualitative method was applied, employing non-participant observation, semi-structured interviews, and document studies as data collection techniques. The data were analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The findings indicate that this program offers a creative, flexible, enjoyable, and contextual learning model aligned with the characteristics of children. The use of songs, mantras, and language games supports learning that meets students’ needs for an engaging and informal atmosphere. However, the implementation still relies on a single teacher, lacks independent integration with the pasraman, and is hindered by low community awareness, limited parental support, and unstable student attendance. Program sustainability is also challenged by the limited availability of teachers, the absence of a standardized curriculum, and minimal budget allocation. This research emphasizes the importance of institutional integration, a flexible yet structured curriculum, and a play-based learning approach in non-formal pasraman education.